El ‘exilio’ uruguayo en Argentina: Intersecciones entre memoria, ciudadanía y democracia - Merenson, Silvina (European Review of Latin American and Caribbean Studies, 2015)
The Uruguayan ‘Exile’ and Argentina: At the Intersections of Memory, Citizenship, and DemocracyThis article explores the interdependencies between ‘memory’, ‘citizenship’, and ‘democracy’ introduced by the Uruguayan ‘exile’ in Argentina together with the coalition Frente Amplio de Uruguay en Argentina (FAUA – Broad Front of Uruguay in Argentina). Starting from a critical review of Transnational Studies and ethnographic fieldwork, this article analyses the political construction of the ‘exile’ and the historical process followed by the FAUA from 1982 up to the present. The article questions the ways in which memories work in regard to the recent past upon value judgements and possible conditions of ‘transnational citizenship’. It maintains that the forms of processing notions of belonging to the political community of origin, as well as those acts of identification and political capital that provide the experience of ‘exile’, offer a privileged point from which to reflect on the ways in which this activism explains the process of democratization in Uruguay.Resumen:Este artículo explora las interdependencias entre ‘memoria’, ‘ciudadanía’ y ‘democracia’ sugeridas por el ‘exilio’ uruguayo en Argentina sumado a la coalición Frente Amplio de Uruguay en Argentina (FAUA). Partiendo de la revisión crítica de los Estudios Transnacionales y del trabajo de campo etnográfico, el artículo analiza la construcción política del ‘exilio’ y el proceso histórico seguido por el FAUA entre 1982 y la actualidad. El artículo se pregunta por los modos en los que operan las memorias acerca del pasado reciente en las valoraciones y condiciones de posibilidad de la ‘ciudadanía transnacional’ y sostiene que las formas de procesar los criterios de pertenencia a la comunidad política de origen, así como con los actos de identificación y el capital político que provee la experiencia del ‘exilio’, ofrecen un punto privilegiado desde el cual reflexionar acerca de los modos en que esta militancia explica el proceso de democratización en Uruguay.